Spectra and pseudospectra : the behavior of nonnormal matrices and operators - Trefethen, Lloyd N. (Lloyd Nicholas) (Princeton University Press, 2005)
"This is the authoritative work on nonnormal matrices and operators, written by the authorities who made them famous. Each of the sixty sections is written as a self-contained essay. Each document is a lavishly illustrated introductory survey of its topic, complete with beautiful numerical experiments and all the right references. The breadth of included topics and the numerous applications that provide links between fields will make this an essential reference in mathematics and related sciences."--Jacket